Guillain-Barre Syndrome Following Falciparum Malaria: A Rare Association - Pan, Koushik; S Chakrabarti; Anupsarkar; Choudhury, Rajdip; Samanta, Tanmay; Mitra, Ritabrata (International Journal of Medical Research, 2013)
Malarial parasite as a cause of Guillain-Barré syndrome (GBS) is very rare and there are only a very few case reports in literature. Here we report a case of acute flaccid quadriparesis with generalised areflexia following malaria caused by P. falciparum. An adult male developed acute lower motor neuron type of quadriparesis following an episode of microscopically proven Plasmodium falciparum malaria. Clinical examination, cerebrospinal fluid analysis, and nerve conduction studies confirmed the diagnosis of GBS, depicting the rare association of GBS following falciparum malaria.